2021
DOI: 10.1021/acs.est.0c08528
|View full text |Cite
|
Sign up to set email alerts
|

Decabromodiphenyl Ether versus Decabromodiphenyl Ethane: Source, Fate, and Influencing Factors in a Coastal Sea Nearing Source Region

Abstract: Both decabromodiphenyl ether (BDE 209) and decabromodiphenyl ethane (DBDPE) are still produced in large quantities in China, especially in the Shandong Province closed to the Bohai Sea (BS). This study conducted a comprehensive investigation of the distribution and budget of brominated flame retardants (BFRs) in the BS. BDE 209 was the predominant BFR in most of the investigated rivers flowing into the BS, although DBDPE exceeded BDE 209 in certain rivers as a result of the replacement of BDE 209 with DBDPE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Despite its relatively smaller length (15 cm), Searsia koefoedi exhibited the highest concentration of all species (16.48 ng g -1 dw) but these results would need to be confirmed as only one pool of 3 individuals was analysed. However, this result is consistent with this species' non-migratory behaviour (at least towards epipelagic waters at night for feeding, but possible migrations deeper into the bathypelagic zone; Novotny, 2018), as DBDPE has been shown to be high in deeper waters (Zhen et al, 2021). The ratio between DBDPE and BDE-209 concentrations has been suggested as a useful tracer of sources and processes, with a higher DBDPE/BDE-209 ratio being observed in deep waters compared to the surface ones because of the higher affinity to fine particles and stability of DBDPE compared to BDE-209 (Zhen et al, 2021).…”
Section: Specific Congener Analysis Reveals Untypical Bfr Profilessupporting
confidence: 82%
See 1 more Smart Citation
“…Despite its relatively smaller length (15 cm), Searsia koefoedi exhibited the highest concentration of all species (16.48 ng g -1 dw) but these results would need to be confirmed as only one pool of 3 individuals was analysed. However, this result is consistent with this species' non-migratory behaviour (at least towards epipelagic waters at night for feeding, but possible migrations deeper into the bathypelagic zone; Novotny, 2018), as DBDPE has been shown to be high in deeper waters (Zhen et al, 2021). The ratio between DBDPE and BDE-209 concentrations has been suggested as a useful tracer of sources and processes, with a higher DBDPE/BDE-209 ratio being observed in deep waters compared to the surface ones because of the higher affinity to fine particles and stability of DBDPE compared to BDE-209 (Zhen et al, 2021).…”
Section: Specific Congener Analysis Reveals Untypical Bfr Profilessupporting
confidence: 82%
“…However, this result is consistent with this species' non-migratory behaviour (at least towards epipelagic waters at night for feeding, but possible migrations deeper into the bathypelagic zone; Novotny, 2018), as DBDPE has been shown to be high in deeper waters (Zhen et al, 2021). The ratio between DBDPE and BDE-209 concentrations has been suggested as a useful tracer of sources and processes, with a higher DBDPE/BDE-209 ratio being observed in deep waters compared to the surface ones because of the higher affinity to fine particles and stability of DBDPE compared to BDE-209 (Zhen et al, 2021). However, using this ratio in biota has limitations and no correlation was found between BDE-209 and DBDPE in our set of samples.…”
Section: Specific Congener Analysis Reveals Untypical Bfr Profilessupporting
confidence: 82%
“…For OPFR input from terrestrial runoff, the decreasing concentrations offshore might also be associated with dilution by offshore seawater, absorption of particles, and degradation effects such as hydrolysis, photolysis, and biodegradation during the oceanic transport. 7 , 35 The ChnMETOP simulated OPFR seawater concentration over the BS ranged from 28.29 ng/L to 955 ng/L (median: 50.65 ng/L). The ChnMETOP modeled median concentration agrees with the Delft3D-WAQ scenario 2 simulation (59.5 ng/L).…”
Section: Resultsmentioning
confidence: 99%
“…Polybrominated diphenyl ethers (PBDEs), excellent flame retardants in spite of the global prohibitions on the production and application for years, have been evidenced to be ubiquitous in the receiving ecosystem. High concentrations in soils (at ng/g–mg/g levels) have raised concerns about crop safety recently. , PBDEs can be accumulated in various tissues of crops through the soil–root–leaf pathway, eventually posing detrimental threats to human health via food consumption. Several studies indicated that plants took up most of PBDEs from the exposure media, with an obvious concentration gradient (root > stem > leaf), and that highly brominated PBDEs were more difficult to be transported. , Our previous investigation showed that ∼0.5% of 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) was accumulated in rice grains and affected the nutritional value of grains . While significant research is dedicated to investigating the absorption, distribution, metabolism, and excretion ( i.e.…”
Section: Introductionmentioning
confidence: 99%